Stable curing material for high-expansibility heavy metal polluted clay and preparation method of stable curing material
By preparing stable cured materials for highly expandable heavy metal contaminated clay, using components such as composite calcium carbide slag pellets and modified adhesives, the problems of poor bonding and insufficient adsorption of cured materials are solved, and stability in high-temperature and humid environments are achieved Performance and efficient adsorption effect, economical and environmentally friendly.
Patent Information
- Application Number
- CN202411354928.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-27
- Publication Date
- 2025-01-03
AI Technical Summary
In the prior art, the solidified components of the stable cured material have poor bonding properties, insufficient adsorption of polluted heavy metal elements, and poor performance in high temperature and humid environments, especially cement-based materials have a great pollution to the environment and are difficult to replace.
Stable curing materials of highly expansive heavy metal contaminated clay, including composite calcium carbide slag pellets, modified binders, alkaline excitation materials, refired magnesium oxide and metakaolin, are prepared through specific process steps to form stable curing materials , use modified adhesives to enhance adhesion and adsorption capabilities, and use industrial waste to reduce costs.
The stability and overall stability of the cured material have been improved, the adsorption performance of heavy metal pollutants has been improved, and good performance is maintained in high temperature and humid environments, with good economic and environmental benefits.
Smart Images

Figure BDA0005063340400000031 
Figure BDA0005063340400000032 
Figure BDA0005063340400000033
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of engineering materials and environmental engineering, and in particular to a stable solidified material of high-expansion heavy metal-contaminated clay and a preparation method thereof. Background Art
[0002] The problem of heavy metal pollution has become increasingly serious in recent years. Heavy metal elements in the soil enter the food chain after being absorbed by farmland crops. At the same time, since the existence form of heavy metals in the soil is easily affected by human activities, the enrichment and migration of heavy metals are becoming more and more serious. Therefore, how to efficiently remediate contaminated soil has become a research focus and hotspot.
[0003] At present, soil pollution remediation methods include physical remediation, chemical remediation and biological remediation. The chemical remediation method is to add chemical reagents to the contaminated soil, and physical and chemical reactions occur in the mixed soil or the pH of the soil is changed, so that the free metal ions are fixed to achieve the purpose of remediation; common chemical remediation methods include fixation stabilization method, common curing agents include volcanic ash materials, cement-based materials and phosphate materials, etc., and among many curing agents, cement curing agents have the advantage of significant curing effect. However, the manufacture of cement consumes a huge amount of resources and emits a large amount of greenhouse gas CO2, which pollutes the ecological environment. Therefore, finding an environmentally friendly curing agent that can replace cement is of great practical significance. In addition, in heavily polluted soils containing multiple heavy metal elements, a combination of multiple stable curing materials is also required to improve its own adsorption performance.
[0004] Patent application CN112876169A discloses a coating slurry composition, a coating slurry aggregate and a preparation method thereof. The coating slurry aggregate comprises aggregate, a coating slurry composition, water and an admixture. The coating slurry composition comprises calcined clay, limestone, gypsum and cement. The admixture is an amphoteric polycarboxylic acid water reducer. Calcined clay and limestone powder are used instead of silicate cement. Cement and gypsum are compounded in specific contents to make the microstructure of the coating slurry composition denser and have a better curing effect. However, the limestone, gypsum and cement matrix in the above-mentioned coating slurry composition are highly polluting to the environment, and it is difficult to form a stable whole without adding the aggregate to the coating slurry composition. How to achieve the stable combination of various components while using industrial waste as the skeleton of the curing material, and how to prepare a stable curing material with strong adsorption and curing properties for polluting heavy metal elements is a technical problem that needs to be solved urgently. In addition, the stable curing material needs to have good hygroscopic properties to ensure that the cured product can still maintain good performance in a high temperature or humid environment.
[0005] In view of the technical defects in this aspect, a solution is now proposed. Summary of the invention
[0006] The purpose of the present invention is to provide a stable solidified material of high-expansion heavy metal contaminated clay and a preparation method thereof, which is used to solve the problems of poor binding of various solidified components and poor adsorption of polluting heavy metal elements in the stable solidified material in the prior art. In addition, how to improve the performance of the stable solidified material in a high temperature and humid environment is also a technical problem that needs to be solved urgently.
[0007] The purpose of the present invention can be achieved by the following technical scheme: a stable solidifying material for high-expansion heavy metal-contaminated clay, which comprises, by weight, 50-60 parts of composite carbide slag pellets, 5-10 parts of modified adhesives, 5-10 parts of alkaline activating materials, 5-10 parts of dead-burned magnesium oxide, 5-10 parts of kaolin and 1-2 parts of polyvinyl alcohol, wherein the alkaline activating material is obtained by mixing calcium oxide and sodium silicate in a mass ratio of 1:1.
[0008] Furthermore, the preparation method of the modified adhesive comprises the following steps:
[0009] A1. At 0-10°C, chlorocyclopropane, methyltrimethoxysilane and iodine powder are mixed to obtain a mixture; the mixture is then refluxed for 2-3 hours at 90-100°C in a nitrogen atmosphere, the gas is discharged, and the mixture is cooled to room temperature to obtain a generated liquid; the generated liquid is distilled at 102-105°C until the volume of the generated liquid remains unchanged, and the organic liquid is collected to obtain an intermediate A;
[0010] Using iodine powder as an activator, chlorocyclopropane and methyltrimethoxysilane undergo a nucleophilic substitution reaction to prepare an organic liquid intermediate A.
[0011] The reaction principle of chlorocyclopropane and methyltrimethoxysilane to obtain intermediate A is as follows:
[0012]
[0013] A2, allyl bromide is dissolved in tetrahydrofuran to obtain an allyl bromide solution; under a nitrogen atmosphere, the allyl bromide solution, transition metal indium and methyltrichlorosilane are mixed, reacted at room temperature for 3-5 hours, and then filtered to obtain a filtrate; the filtrate is distilled under reduced pressure to obtain allyl chlorosilane liquid;
[0014] Allyl bromide and methyltrichlorosilane undergo allylation reaction with transition metal indium as a catalyst. Transition metal indium itself can serve as a mild reducing agent, so that the olefin group in allyl bromide will not be destroyed and dehalogenation reaction will not occur, thereby obtaining allyl chlorosilane liquid.
[0015] The reaction equation of allyl bromide and methyltrichlorosilane is as follows:
[0016]
[0017] A3. Mix the intermediate A and allyl chlorosilane liquid, and react at a constant temperature of 50-60° C. for 2-3 hours to obtain a modified adhesive.
[0018] The small molecule cyclopropyl of the organic liquid intermediate A and allyl chlorosilane undergo electrophilic substitution reaction to prepare a modified adhesive.
[0019] The reaction principle of organic liquid intermediate A and allyl chlorosilane is as follows:
[0020]
[0021] Furthermore, in step A1, the usage ratio of chlorocyclopropane, methyltrimethoxysilane and iodine powder is 5-10mL:15-20mL:1-2g; in step A2, the usage ratio of allyl bromide and tetrahydrofuran is 12-15mL:50mL; 50mL of allyl bromide solution, transition metal indium and methyltrichlorosilane:0.3-0.5g:15-20g; in step A3, the usage ratio of intermediate A and allyl chlorosilane is 5-10mL:10-13mL.
[0022] Furthermore, the method for preparing the composite carbide slag pellets comprises the following steps:
[0023] B1, fly ash is ground to a particle size of 0.01-0.02 mm to obtain fly ash powder; carbide slag is ground to a particle size of 0.1-0.2 mm to obtain carbide slag powder;
[0024] B2, polyetheramine D-230 and KH560 are mixed, reacted at 90-100° C. for 3-4 hours under a nitrogen atmosphere to obtain an organic matter; the organic matter and methanol are mixed uniformly in a mass ratio of 1:1 to obtain a 50%wt mixed solution, which is a modifier;
[0025] The amino group in the polyetheramine D-230 and the epoxy group in the KH560 undergo a ring-opening addition reaction to prepare a modifier.
[0026] The reaction formula of polyetheramine D-230 and KH560 is as follows:
[0027]
[0028] Among them, the CAS number of polyetheramine D-230 is 9046-10-0, the total amine value is 460-490, and the molecular weight is 500.
[0029] B3, fly ash powder, carbide slag powder, modifier and deionized water are stirred evenly to obtain a mixture; the mixture is added into the particle composite system PCS, and treated at 5000r / min for 15-20min to obtain composite pellets;
[0030] B4. In an atmosphere of 99% high-purity argon, the composite pellets are added into a high-temperature tubular furnace; the reactor of the high-temperature tubular furnace is heated to the first stage and reacted at a constant temperature for 10-20 minutes; then the temperature is heated to the second stage and reacted at a constant temperature for 10-20 minutes, and then the temperature is stopped to allow the high-temperature tubular furnace reactor to cool naturally to room temperature, and the solid is taken out to obtain the composite carbide slag pellets.
[0031] Furthermore, in step B2, the usage ratio of polyetheramine D-230 and KH560 is 20-30mL:30-40mL; in step B3, the usage ratio of fly ash powder, carbide slag powder, modifier and deionized water is 15-25g:50-60g:5-10g:10-15g.
[0032] Furthermore, in step B4, the heating rate of the first stage is 8°C / min, from room temperature to 600°C; the heating rate of the second stage is 5°C / min, from 600°C to 800°C.
[0033] The present invention also proposes a method for preparing a stable solidified material of high-expansion heavy metal-contaminated clay, comprising the following steps:
[0034] The modified adhesive, composite carbide slag pellets, alkaline activating material, dead-burned magnesium oxide, metakaolin and polyvinyl alcohol are uniformly mixed to obtain a stable solidification material for high-expansion heavy metal-contaminated clay.
[0035] The present invention has the following beneficial effects:
[0036] 1. The stable solidified material prepared by the present invention is an inorganic solidified material, with composite carbide slag pellets, dead-burned magnesium oxide and kaolin as the main solidified materials, calcium oxide and sodium silicate added as alkaline excitation materials, and assisted by a modified adhesive to form a stable solidified material, and chlorocyclopropane and methyltrimethoxysilane react to prepare a coupling agent intermediate A containing a small molecule cyclopropyl group; the present invention modifies the intermediate A with allyl chlorosilane, and the obtained modified adhesive contains polysiloxy groups, which can react with a large number of hydroxyl groups contained in polyvinyl alcohol, further enhancing the bonding performance of the stable solidified material, so that the main solidified material and the alkaline excitation material components are closely combined, and the stability and integrity of the prepared stable solidified material are improved. In addition, the double bonds in the modified adhesive contain lone pairs of electrons, and these lone pairs of electrons can form coordination bonds with the empty orbitals of polluting heavy metal ions, thereby improving the adsorption performance of heavy metal pollutants.
[0037] 2. The chemical composition of industrial waste carbide slag includes SiO2, Ca(OH)2, CaCO3 and CaO, and the main components of fly ash include SiO2, Al2O3, Fe2O3 and CaO. Mixing carbide slag and fly ash can replace cement for soil repair. The particle size difference between fly ash and carbide slag is ten times. During the blending process of fly ash powder and carbide slag powder, fly ash can be filled into the slag as a reinforcing material; fly ash powder and carbide slag powder are formed into pellets by a granular composite system PCS. The mixed powder is continuously subjected to strong impact, stirring and crushing, and lattice defects are continuously generated in large quantities inside the large grains. The organizational structure of the powder is gradually refined, and finally different components penetrate and diffuse into each other to achieve close bonding at the atomic level, thereby obtaining dispersed embedded pellets, and then the pellets are subjected to secondary high-temperature calcination in a high-temperature tubular furnace to prepare composite carbide slag pellets. The modifier obtained by modifying KH560 with polyetheramine D-230 has an increased number of silicon-oxygen bonds, which can improve its own modification performance, thereby increasing the bonding density of fly ash powder and carbide slag powder.
[0038] 3. Carbide slag, dead-burned magnesium oxide and kaolin are used as the main solidifying materials. The main solidifying materials can undergo hydrolysis and hydration reactions with water in the soil to generate gel-like polyhydrates. On the one hand, these hydrates can harden themselves to form a skeleton, and on the other hand, they can cement soil particles and fill the tiny holes between the soil to form a stable network structure, thereby enhancing soil stability. Since the main solidifying materials contain a certain amount of cations such as calcium ions, calcium oxide and sodium silicate are used as the alkaline excitation system. In the alkaline excitation system, the cation price enters the condensation chain and reduces the degree of polymerization. Therefore, the alkaline excitation The material is easy to form alkali-activated gel material aluminum silicate, and finally forms a composite gelling system in which gel and other products coexist; in addition, the present invention uses carbide slag, dead-burned magnesium oxide and kaolin, which are all industrial wastes, with lower costs and the ability to treat waste with waste, with good economic and environmental benefits. In order to expand the use of stable solidifying materials in high temperature and humid environments, a small amount of polyvinyl alcohol is added to the above-mentioned stable solidifying materials. Polyvinyl alcohol has high expansibility and can quickly swell into colloidal particles in water, thereby absorbing a large amount of water and improving its application ability in high temperature and humid environments. DETAILED DESCRIPTION
[0039] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0040] Example 1
[0041] This embodiment provides a method for preparing a modified binder for a stable solidification material of high-expansion heavy metal-contaminated clay, comprising the following steps:
[0042] A1. A 100mL four-necked flask is connected with a reflux condenser, a gas introduction tube, a thermometer and an agitator, and the four-necked flask is transferred to a water bath, and the temperature of the water bath is set to 0°C; 5mL of chlorocyclopropane, 15mL of methyltrimethoxysilane and 1g of iodine powder are added to the four-necked flask to obtain a mixture; the interface of the four-necked flask is sealed, and the four-necked flask is evacuated and filled with nitrogen three times continuously, and then the temperature of the water bath is adjusted to 90°C, and reflux reaction is carried out at this temperature for 2h. After the reaction is completed, the gas in the four-necked flask is discharged; the four-necked flask is cooled to room temperature to obtain a generated liquid; the generated liquid is distilled at 102°C until the volume of the organic liquid remains unchanged, and the organic liquid is collected to obtain intermediate A.
[0043] A2. 12 mL of allyl bromide was dissolved in 50 mL of tetrahydrofuran to obtain an allyl bromide solution; one end of a 250 mL round-bottomed double-necked flask was connected to a reflux condenser and the other end was connected to an air guide tube, a stirring bar was arranged inside the round-bottomed double-necked flask, nitrogen was introduced into the round-bottomed double-necked flask until all the air in the round-bottomed double-necked flask was expelled, so that it was placed in a nitrogen atmosphere; then 50 mL of the allyl bromide solution was transferred to the round-bottomed double-necked flask, and 0.3 g of transition metal indium was added and mixed evenly; then 15 g of methyltrichlorosilane was introduced, the round-bottomed double-necked flask was sealed, and the reaction was carried out at room temperature for 3 h with a speed of 100 r / min, and then filtered to obtain a filtrate; the filtrate was distilled under reduced pressure to obtain allyl chlorosilane liquid.
[0044] A3. Transfer 5 mL of organic liquid intermediate A and 10 mL of allyl chlorosilane liquid to a 50 mL round-bottom double-necked flask, and react at a constant temperature of 50° C. for 2 h to obtain a modified adhesive.
[0045] Example 2
[0046] This embodiment provides a method for preparing a modified binder for a stable solidification material of high-expansion heavy metal-contaminated clay, comprising the following steps:
[0047] A1. A 100mL four-necked flask was connected with a reflux condenser, a gas introduction tube, a thermometer and an agitator, and the four-necked flask was transferred to a water bath, and the temperature of the water bath was set to 5°C; 8mL of chlorocyclopropane, 16mL of methyltrimethoxysilane and 1g of iodine powder were added to the four-necked flask to obtain a mixture; the interface of the four-necked flask was sealed, and the four-necked flask was evacuated and filled with nitrogen three times continuously, and then the temperature of the water bath was adjusted to 92°C, and refluxed at this temperature for 2.5h. After the reaction was completed, the gas in the four-necked flask was discharged; the four-necked flask was cooled to room temperature to obtain a generated liquid; the generated liquid was distilled at 103°C until the volume of the organic liquid remained unchanged, and the organic liquid was collected to obtain an intermediate A.
[0048] A2, 13mL of allyl bromide was dissolved in 50mL of tetrahydrofuran to obtain an allyl bromide solution; one end of a 250mL round-bottomed double-necked flask was connected to a reflux condenser and the other end was connected to an air guide tube, a stirring bar was set inside the round-bottomed double-necked flask, nitrogen was introduced into the round-bottomed double-necked flask until all the air in the round-bottomed double-necked flask was expelled, so that it was placed in a nitrogen atmosphere; then 50mL of the allyl bromide solution was transferred to the round-bottomed double-necked flask, and 0.4g of transition metal indium was added and mixed evenly; then 16g of methyltrichlorosilane was introduced, the round-bottomed double-necked flask was sealed, and the reaction was carried out at room temperature for 4h with a rotation speed of 150r / min, and then filtered to obtain a filtrate; the filtrate was distilled under reduced pressure to obtain allyl chlorosilane liquid.
[0049] A3. Transfer 6 mL of organic liquid intermediate A and 12 mL of allyl chlorosilane liquid to a 50 mL round-bottom double-necked flask, and react at a constant temperature of 55° C. for 2.5 h to obtain a modified adhesive.
[0050] Example 3
[0051] This embodiment provides a method for preparing a modified binder for a stable solidification material of high-expansion heavy metal-contaminated clay, comprising the following steps:
[0052] A1. A 100mL four-necked flask was connected with a reflux condenser, a gas introduction tube, a thermometer and an agitator, and the four-necked flask was transferred to a water bath, and the temperature of the water bath was set to 10°C; 10mL of chlorocyclopropane, 20mL of methyltrimethoxysilane and 2g of iodine powder were added to the four-necked flask to obtain a mixture; the interface of the four-necked flask was sealed, and the four-necked flask was evacuated and filled with nitrogen three times continuously, and then the temperature of the water bath was adjusted to 100°C, and refluxed at this temperature for 3h. After the reaction was completed, the gas in the four-necked flask was discharged; the four-necked flask was cooled to room temperature to obtain a generated liquid; the generated liquid was distilled at 105°C until the volume of the organic liquid remained unchanged, and the organic liquid was collected to obtain an intermediate A.
[0053] A2. 15 mL of allyl bromide was dissolved in 50 mL of tetrahydrofuran to obtain an allyl bromide solution; one end of a 250 mL round-bottomed double-necked flask was connected to a reflux condenser and the other end was connected to an air guide tube, a stirring bar was arranged inside the round-bottomed double-necked flask, nitrogen was introduced into the round-bottomed double-necked flask until all the air in the round-bottomed double-necked flask was expelled, so that it was placed in a nitrogen atmosphere; then 50 mL of the allyl bromide solution was transferred to the round-bottomed double-necked flask, and 0.5 g of transition metal indium was added and mixed evenly; then 20 g of methyltrichlorosilane was introduced, the round-bottomed double-necked flask was sealed, and the reaction was carried out at room temperature for 5 h with a rotation speed of 200 r / min, and then filtered to obtain a filtrate; the filtrate was distilled under reduced pressure to obtain allyl chlorosilane liquid.
[0054] A3. Transfer 10 mL of organic liquid intermediate A and 13 mL of allyl chlorosilane liquid to a 50 mL round-bottom double-necked flask, and react at a constant temperature of 60° C. for 3 h to obtain a modified adhesive.
[0055] Example 4
[0056] This embodiment provides a method for preparing composite carbide slag pellets for use as a stable solidification material for high-expansion heavy metal-contaminated clay, comprising the following steps:
[0057] B1. Add fly ash into a rotary grinder and grind it to a particle size of 0.01 mm to obtain fly ash powder; add carbide slag into a rotary grinder and grind it to a particle size of 0.1 mm to obtain carbide slag powder.
[0058] B2, 20mL of polyetheramine D-230 and 30mL of KH560 were added to a 250mL two-necked round-bottom flask, and nitrogen was introduced into the three-necked round-bottom flask at a flow rate of 100mL / min for 5min to replace the air in the three-necked round-bottom flask. The three-necked round-bottom flask was then transferred to a microwave reactor and reacted at 90°C for 3h to obtain an organic matter. The organic matter and methanol were mixed uniformly in a mass ratio of 1:1 to obtain a 50%wt mixed solution, which was the modifier.
[0059] B3, according to weight parts, 15g of fly ash powder, 50g of carbide slag powder, 5g of modifier and 10g of deionized water were added to a constant temperature magnetic stirrer and stirred evenly to obtain a mixed material. The mixed material was added to the particle composite system PCS, the system rotor speed was 5000r / min, the processing time was 15min, and composite pellets were obtained.
[0060] B4. Fill the reactor of the high-temperature tubular furnace with argon gas, and the argon gas in the reactor is ≥99%, so that the reactor is in an atmosphere of high-purity argon gas; then add the composite pellets into the reactor of the high-temperature tubular furnace, and heat the reactor of the high-temperature tubular furnace from room temperature to 600°C at a rate of 5°C / min, and react at a constant temperature for 10 minutes; then heat the reactor from 600°C to 800°C at a rate of 5°C / min, and react at a constant temperature for 10 minutes, and then stop heating; the reactor of the high-temperature tubular furnace is naturally cooled to room temperature, and the solid is taken out to obtain the composite carbide slag pellets.
[0061] Example 5
[0062] This embodiment provides a method for preparing composite carbide slag pellets for use as a stable solidification material for high-expansion heavy metal-contaminated clay, comprising the following steps:
[0063] B1. Add fly ash into a rotary grinder and grind it to a particle size of 0.012 mm to obtain fly ash powder; add carbide slag into a rotary grinder and grind it to a particle size of 0.2 mm to obtain carbide slag powder.
[0064] B2, 25mL of polyetheramine D-230 and 35mL of KH560 were added to a 250mL two-necked round-bottom flask, and nitrogen was introduced into the three-necked round-bottom flask at a flow rate of 100mL / min for 5min to replace the air in the three-necked round-bottom flask. The three-necked round-bottom flask was then transferred to a microwave reactor and reacted at 95°C for 3.5h to obtain an organic matter. The organic matter and methanol were mixed uniformly in a mass ratio of 1:1 to obtain a 50%wt mixed solution, which was the modifier.
[0065] B3, according to weight parts, 20g of fly ash powder, 55g of carbide slag powder, 8g of modifier and 12g of deionized water were added to a constant temperature magnetic stirrer and stirred evenly to obtain a mixed material. The mixed material was added to the particle composite system PCS, the system rotor speed was 5000r / min, the processing time was 16min, and composite pellets were obtained.
[0066] B4. Fill the reactor of the high-temperature tubular furnace with argon gas, and the argon gas in the reactor is ≥99%, so that the reactor is in an atmosphere of high-purity argon gas; then add the composite pellets into the reactor of the high-temperature tubular furnace, and heat the reactor of the high-temperature tubular furnace from room temperature to 600°C at a rate of 8°C / min, and react at a constant temperature for 15 minutes; then heat the reactor from 600°C to 800°C at a rate of 5°C / min, and react at a constant temperature for 15 minutes, and then stop heating; the reactor of the high-temperature tubular furnace is naturally cooled to room temperature, and the solid is taken out to obtain the composite carbide slag pellets.
[0067] Example 6
[0068] This embodiment provides a method for preparing composite carbide slag pellets for use as a stable solidification material for high-expansion heavy metal-contaminated clay, comprising the following steps:
[0069] B1. Add fly ash into a rotary grinder and grind it to a particle size of 0.02 mm to obtain fly ash powder; add carbide slag into a rotary grinder and grind it to a particle size of 0.2 mm to obtain carbide slag powder.
[0070] B2, 30mL of polyetheramine D-230 and 40mL of KH560 were added to a 250mL two-necked round-bottom flask, and nitrogen was introduced into the three-necked round-bottom flask at a flow rate of 100mL / min for 5min to replace the air in the three-necked round-bottom flask. The three-necked round-bottom flask was then transferred to a microwave reactor and reacted at 100°C for 4h to obtain an organic matter. The organic matter and methanol were mixed uniformly in a mass ratio of 1:1 to obtain a 50%wt mixed solution, which was the modifier.
[0071] B3, according to weight parts, 25g of fly ash powder, 60g of carbide slag powder, 10g of modifier and 15g of deionized water were added to a constant temperature magnetic stirrer and stirred evenly to obtain a mixed material. The mixed material was added to the particle composite system PCS, the system rotor speed was 5000r / min, the processing time was 20min, and composite pellets were obtained.
[0072] B4. Fill the reactor of the high-temperature tubular furnace with argon gas, and the argon gas in the reactor is ≥99%, so that the reactor is in an atmosphere of high-purity argon gas; then add the composite pellets into the reactor of the high-temperature tubular furnace, and heat the reactor of the high-temperature tubular furnace from room temperature to 600°C at a rate of 10°C / min, and react at a constant temperature for 20 minutes; then heat the reactor from 600°C to 800°C at a rate of 5°C / min, and react at a constant temperature for 20 minutes, and then stop heating; the reactor of the high-temperature tubular furnace is naturally cooled to room temperature, and the solid is taken out to obtain the composite carbide slag pellets.
[0073] Example 7
[0074] This embodiment provides a method for preparing a stable solidified material of high-expansion heavy metal-contaminated clay, comprising the following steps:
[0075] According to weight parts, 5 parts of the modified binder prepared in Example 1, 50 parts of the composite carbide slag pellets prepared in Example 4, 5 parts of alkaline excitation material, 5 parts of dead-burned magnesium oxide, 5 parts of metakaolin and 1 part of polyvinyl alcohol were uniformly mixed to obtain a stable solidification material for high-expansion heavy metal contaminated clay. Among them, the alkaline excitation material is obtained by mixing calcium oxide and sodium silicate in a mass ratio of 1:1.
[0076] Example 8
[0077] This embodiment provides a method for preparing a stable solidified material of high-expansion heavy metal-contaminated clay, comprising the following steps:
[0078] According to weight parts, 8 parts of the modified binder prepared in Example 2, 55 parts of the composite carbide slag pellets prepared in Example 5, 8 parts of alkaline excitation material, 8 parts of dead-burned magnesium oxide, 8 parts of metakaolin and 1 part of polyvinyl alcohol were uniformly mixed to obtain a stable solidification material for high-expansion heavy metal contaminated clay. Among them, the alkaline excitation material is obtained by mixing calcium oxide and sodium silicate in a mass ratio of 1:1.
[0079] Example 9
[0080] This embodiment provides a method for preparing a stable solidified material of high-expansion heavy metal-contaminated clay, comprising the following steps:
[0081] According to weight parts, 10 parts of the modified binder prepared in Example 3, 60 parts of the composite carbide slag pellets prepared in Example 6, 10 parts of alkaline excitation material, 10 parts of dead-burned magnesium oxide, 10 parts of metakaolin and 2 parts of polyvinyl alcohol were uniformly mixed to obtain a stable solidification material for high-expansion heavy metal contaminated clay. Among them, the alkaline excitation material is obtained by mixing calcium oxide and sodium silicate in a mass ratio of 1:1.
[0082] Comparative Example 1
[0083] The difference between this comparative example and Example 9 is that the composite carbide slag pellets are replaced by carbide slag of equal mass.
[0084] Comparative Example 2
[0085] The difference between this comparative example and Example 9 is that the modified binder is replaced by the intermediate A of equal mass.
[0086] Comparative Example 3
[0087] The difference between this comparative example and Example 9 is that the modified binder is replaced by an equal mass of allyl chlorosilane liquid.
[0088] Performance Test:
[0089] Highly expansive heavy metal contaminated clay was collected from the soil around a smelter in Yixing, Jiangsu. The sampling depth was 0-30 cm. The soil samples were mainly contaminated by Pb, Zn and Cr. The soil samples were air-dried, crushed, passed through a 2 mm sieve, and then bagged and sealed for storage as test soil samples.
[0090] The stable solidified materials of high-expansion heavy metal-contaminated clay prepared in Examples 7-9 and Comparative Examples 1-3 were sequentially mixed into the test soil samples according to proportion, and a certain amount of water was added so that the moisture content of the final sample was 25%. The final sample was stirred evenly and poured into a PVC mold coated with vaseline inside. The diameter of the mold was 40 mm and the height of the mold was 80 mm. The sample was then demolded and sampled after standing for 24 hours and placed in a constant temperature and humidity incubator for curing.
[0091] 1. According to ASTM D4219-08 "Test method for unconfined compressive strength index test of chemical grouting material soil", a load-bearing tester equipped with displacement and pressure sensors was used to detect the values of the 7-day unconfined compressive strength of the samples prepared in Examples 7-9 and Comparative Examples 1-3. Three parallel samples were used for each test. The unconfined compressive strength of the group was the average value of the strengths of the three parallel samples. In order to ensure the accuracy of each group of test results, if the strength deviation of the three parallel samples exceeded 10%, they should be discarded immediately.
[0092] 2. According to USEPA1315, a leaching test was conducted on heavy metal contaminated clay, in which the pH value of the leaching solution was set to 7, and the leaching efficiency of Pb, Zn and Cr was tested. The specific test results are shown in Table 1.
[0093] Table 1-Performance test data of samples
[0094]
[0095] Data Analysis:
[0096] Comparative analysis of the data in Table 1 shows that the stable solidified materials of high expansibility heavy metal contaminated clay prepared by Examples 7-9 of the present invention have excellent mechanical properties. When preparing composite carbide slag pellets, fly ash is used as a reinforcing agent for carbide slag. Through a molding spherical process and a high-temperature calcination process, lattice defects are utilized to achieve mutual penetration and diffusion between components, thereby obtaining high-strength and high-density composite carbide slag pellets, which is manifested as a high value of the 7-day unconfined compressive strength of the prepared stable solidified material. However, in Comparative Example 1, carbide slag of equal mass is used to replace the composite carbide slag pellets, thereby reducing the values of the unconfined compressive strength of the composite carbide slag pellets and the stable solidified materials.
[0097] The stabilized solidified materials of high-expansion heavy metal-contaminated clay prepared in Examples 7-9 of the present invention have excellent adsorption and solidification properties for heavy metal contamination elements Pb, Zn and Cd, as shown in the toxicity leaching test, the toxicity leaching values of Pb, Zn and Cd are relatively low. However, in Comparative Example 2, the modified binder is replaced by intermediate A, and in Comparative Example 3, the modified binder is replaced by allyl chlorosilane, which reduces the number of siloxy groups in the modified binder, reduces the structural stability of the stabilized solidified materials, and reduces their adsorption properties, which is shown in the toxicity leaching test, the toxicity leaching values of Pb, Zn and Cd are relatively low.
[0098] The above contents are merely examples and explanations of the structure of the present invention. The technicians in this technical field may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the structure of the invention or exceed the scope defined by the claims, they should all fall within the protection scope of the present invention.
[0099] In the description of this specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.
[0100] The preferred embodiments of the present invention disclosed above are only used to help explain the present invention. The preferred embodiments do not describe all the details in detail, nor do they limit the invention to only specific implementation methods. Obviously, many modifications and changes can be made according to the content of this specification. This specification selects and specifically describes these embodiments in order to better explain the principles and practical applications of the present invention, so that those skilled in the art can understand and use the present invention well. The present invention is limited only by the claims and their full scope and equivalents.
Claims
1. A stable solidification material for high-expansion heavy metal-contaminated clay, characterized in that: In parts by weight, it comprises 50-60 parts of composite carbide slag pellets, 5-10 parts of modified adhesive, 5-10 parts of alkaline activating material, 5-10 parts of dead-burned magnesium oxide, 5-10 parts of kaolin and 1-2 parts of polyvinyl alcohol; the alkaline activating material is obtained by mixing calcium oxide and sodium silicate in a mass ratio of 1:
1.
2. The stabilized solidified material for high-expansion heavy metal-contaminated clay according to claim 1, characterized in that: The preparation method of the modified adhesive comprises the following steps: A1. At 0-10°C, chlorocyclopropane, methyltrimethoxysilane and iodine powder are mixed to obtain a mixture; the mixture is then refluxed for 2-3 hours at 90-100°C in a nitrogen atmosphere, the gas is discharged, and the mixture is cooled to room temperature to obtain a generated liquid; the generated liquid is distilled at 102-105°C until the volume of the organic liquid remains unchanged, and the organic liquid is collected to obtain an intermediate A; A2, allyl bromide is dissolved in tetrahydrofuran to obtain an allyl bromide solution; under a nitrogen atmosphere, the allyl bromide solution, transition metal indium and methyltrichlorosilane are mixed, reacted at room temperature for 3-5 hours, and then filtered to obtain a filtrate; the filtrate is distilled under reduced pressure to obtain allyl chlorosilane liquid; A3. Mix the intermediate A and allyl chlorosilane liquid, and react at a constant temperature of 50-60° C. for 2-3 hours to obtain a modified adhesive.
3. The stabilized solidified material for high-expansion heavy metal-contaminated clay according to claim 2, characterized in that: In step A1, the usage ratio of chlorocyclopropane, methyltrimethoxysilane and iodine powder is 5-10mL:15-20mL:1-2g; in step A2, the usage ratio of allyl bromide and tetrahydrofuran is 12-15mL:50mL; 50mL of allyl bromide solution, transition metal indium and methyltrichlorosilane:0.3-0.5g:15-20g; in step A3, the usage ratio of intermediate A and allyl chlorosilane is 5-10mL:10-13mL.
4. The stabilized solidified material for high-expansion heavy metal-contaminated clay according to claim 1, characterized in that: The method for preparing the composite carbide slag pellets comprises the following steps: B1, fly ash is ground to a particle size of 0.01-0.02 mm to obtain fly ash powder; carbide slag is ground to a particle size of 0.1-0.2 mm to obtain carbide slag powder; B2, polyetheramine D-230 and KH560 are mixed, reacted at 90-100°C for 3-4 hours under a nitrogen atmosphere to obtain an organic matter; the organic matter and methanol are mixed evenly in a mass ratio of 1:1 to obtain a 50%wt mixed solution, which is a modifier; B3, fly ash powder, carbide slag powder, modifier and deionized water are stirred evenly to obtain a mixture; the mixture is added into the particle composite system PCS, and treated at 5000r / min for 15-20min to obtain composite pellets; B4. In an atmosphere of high-purity argon gas of more than 99%, the composite pellets are added into a high-temperature tubular furnace; the reactor of the high-temperature tubular furnace is heated to the first stage, and the reaction is carried out at a constant temperature for 10-20 minutes; the temperature is then heated to the second stage, and the reaction is carried out at a constant temperature for 10-20 minutes, and then the temperature is stopped to allow the high-temperature tubular furnace reactor to cool naturally to room temperature, and the solid is taken out to obtain the composite carbide slag pellets.
5. The stabilized solidified material for high-expansion heavy metal-contaminated clay according to claim 4, characterized in that: In step B2, the usage ratio of polyetheramine D-230 and KH560 is 20-30mL:30-40mL; in step B3, the usage ratio of fly ash powder, carbide slag powder, modifier and deionized water is 15-25g:50-60g:5-10g:10-15g.
6. The stabilized solidified material for high-expansion heavy metal-contaminated clay according to claim 4, characterized in that: In step B4, the heating rate of the first stage is 8°C / min, from room temperature to 600°C; the heating rate of the second stage is 5°C / min, from 600°C to 800°C.
7. A method for preparing a stable solidified material of high-expansion heavy metal-contaminated clay according to any one of claims 1 to 6, characterized in that: The following steps are involved: The modified adhesive, composite carbide slag pellets, alkaline activating material, dead-burned magnesium oxide, metakaolin and polyvinyl alcohol are uniformly mixed to obtain a stable solidification material for high-expansion heavy metal-contaminated clay.
Citation Information
Cited By
Method for preparing adsorbent from clay minerals and carbide slag
CN120437953A
A method for preparing an adsorbent using clay minerals and carbide slag
CN120437953B